A Study of Callers to a Telephone Counseling Service. (October 2021) - Dadfar, Mahboubeh; Lester, David
Telephone counseling is an inexpensive method of providing counseling and crisis intervention in response to some of the mental health needs of the community. It can be provided at a counseling center or other unit with the purpose of providing mental health counseling for callers. The aim of this study was to investigate types of problems and interventions for callers at a telephone counseling service in Tehran, Iran. The data were collected using the records of 82 callers to the Telephone Counseling Center of the School of Behavioral Sciences and Mental Health-Tehran Institute of Psychiatry, affiliated with Iran University of Medical Sciences. The mean the number of calls made by callers was 1.53. The most common problems presented were marital and family conflicts (28.4%), mood disorders (24.3%), interpersonal and communication problems (17%), and behavioral problems of children (15.8%). Counselors offered psychosocial/educational advice (36.5%), recommendations for taking medications (26.8%), recommendations for in-person/individual counseling or family counseling (25.6%), and behavior therapy techniques (17%). Recommendations are made for the evaluation, structure, and process of telephone counseling services and for training telephone counselors in Iran.